2018
DOI: 10.3390/brainsci8030045
|View full text |Cite
|
Sign up to set email alerts
|

l-Carnitine Modulates Epileptic Seizures in Pentylenetetrazole-Kindled Rats via Suppression of Apoptosis and Autophagy and Upregulation of Hsp70

Abstract: l-Carnitine is a unique nutritional supplement for athletes that has been recently studied as a potential treatment for certain neuropsychiatric disorders. However, its efficacy in seizure control has not been investigated. Sprague Dawley rats were randomly assigned to receive either saline (Sal) (negative control) or pentylenetetrazole (PTZ) 40 mg/kg i.p. × 3 times/week × 3 weeks. The PTZ group was further subdivided into two groups, the first received oral l-carnitine (l-Car) (100 mg/kg/day × 4 weeks) (PTZ +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 61 publications
(70 reference statements)
4
27
0
Order By: Relevance
“…Previous studies investigated and confirmed the role of oxidative stress, apoptosis and heat shock proteins in the pathogenic mechanisms of epilepsy [6,7]. Gupta et al [8] and Hussein et al [6,7] demonstrated a significant increase in malondialdehyde (MDA) with a significant reduction in reduced glutathione (GSH) levels and catalase (CAT) activity suggesting enhanced oxidative stress in the brain tissues of epileptic rats. Also, the role of apoptosis and its signaling pathways in seizure-induced neuronal cell deaths has been demonstrated in previous experimental studies [7,9].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies investigated and confirmed the role of oxidative stress, apoptosis and heat shock proteins in the pathogenic mechanisms of epilepsy [6,7]. Gupta et al [8] and Hussein et al [6,7] demonstrated a significant increase in malondialdehyde (MDA) with a significant reduction in reduced glutathione (GSH) levels and catalase (CAT) activity suggesting enhanced oxidative stress in the brain tissues of epileptic rats. Also, the role of apoptosis and its signaling pathways in seizure-induced neuronal cell deaths has been demonstrated in previous experimental studies [7,9].…”
Section: Introductionmentioning
confidence: 92%
“…Details of brain tissue homogenization, tissues lysis, PAGE electrophoresis and membrane transfer and incubation with the primary and secondary antibodies were mentioned in our previous work [7]. The primary antibodies of cleaved caspase-3 (MW 17 and 19 kDa, product No.…”
Section: The Expression Of Caspase-3 and β-Catenin Proteins In Hippocmentioning
confidence: 99%
See 1 more Smart Citation
“…CAT activity in the hippocampal supernatant was estimated according to the method illustrated by Aebi. 34 In order to evaluate the CAT activity, the enzymatic reaction mixture (total volume 1 mL) contained 50…”
Section: Catalase (Cat) Activitymentioning
confidence: 99%
“…49 It has been shown that neuronal cells are able to produce HSPs. Accumulative evidences reported the relationship between the development of epileptic seizures and the upregulation of Hsp70 in animal models 50 and in humans. 51 The authors described the upregulation of Hsp70 as a protective effect potentiated to protect neurons against hyperexcitability coupled with the development of epileptic seizures.…”
Section: Dovepressmentioning
confidence: 99%